Off-label drug use in China after the Physician Law (2021): legal challenges and solutions - Liang, Shenbao; Cai, Fanxian (Frontiers in Pharmacology, 2025)
IntroductionIn 2021 China enacted the Physician Law, which specifically outlines the legal requirements for off-label drug use in Article 29. Legislators, medical institutions, and judicial authorities all hoped that this new regulation would effectively reduce illegal off-label drug use. However, many violations still occurred in medical practice even after the enactment of the Physician Law, leading to judicial cases. This article examines the current state of off-label drug use in China, and the legal liability risks faced by medical institutions.MethodsThis study investigates data from two main aspects: (1) judicial decisions related to off-label drug use; and (2) surveys associated with off-label drug use from medical institutions. Systematic literature search and descriptive data analysis was conducted in this paper.ResultsThis article identifies three main forms of non-compliant off-label drug use: first, insufficient evidence-based justification; second, deficiencies in the informed consent process; and third, the lack of an internal review system. These are also the primary factors leading to legal liability for medical institutions.DiscussionFrom a legal doctrinal perspective, the article concludes by elaborating on how each legal requirement should be met. Our research provides insights into the factors that lead to legal liability for off-label drug use and examines how physicians and medical institutions can avoid such liability.